Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1016/j.jval.2018.07.645
|View full text |Cite
|
Sign up to set email alerts
|

Economic Burden of Needle-Stick Injury Among Healthcare Workers in China

Abstract: groups based on 2014 OECD GDP purchasing power parity (PPP); High, Middle and low income countries. Pharma Price Information (PPI) data and Ministry of Health, Labour and Welfare data were used for European and Japanese drug prices, respectively. Korean reimbursement prices and sales volume in 2016 is used for Korean prices. Prices were compared in two different ways; simple average price ratio compared with Korean average price and Laspeyres index where Korean volume weight was applied to conduct 1:1 comparis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In China, although guidelines for the prevention of occupational BBF exposure have been proposed (see Table S1), governmental regulations have yet to be established through legislative procedures to enforce the management of BBF occupational exposure [11][12][13][14][15]. Consequently, the incidence of BBF exposure among healthcare staff is significantly higher in China than in other countries with specific governmental rules [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In China, although guidelines for the prevention of occupational BBF exposure have been proposed (see Table S1), governmental regulations have yet to be established through legislative procedures to enforce the management of BBF occupational exposure [11][12][13][14][15]. Consequently, the incidence of BBF exposure among healthcare staff is significantly higher in China than in other countries with specific governmental rules [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, very limited research has been performed to determine BBF occupational exposure cost in China. In 2018, Zhang and colleagues estimated that one needlestick injury would trigger a post-exposure management cost of RMB 515 (USD 78) in China, but this result was based on data from foreign countries and eight opinion leaders [19], and thus lacked data of China's healthcare system. In 2019, Zhao and colleagues reported that one insulin injection-related needlestick injury costs between RMB 1884 (USD 285) and RMB 2389 (USD 361) [25].…”
Section: Introductionmentioning
confidence: 99%